1999
DOI: 10.1016/s0014-5793(99)01364-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of novel polymorphisms in the CYP2A locus: implications for nicotine metabolism

Abstract: The polymorphic human cytochrome P450 2A6 (CYP2A6) metabolises a number of drugs, activates a variety of precarcinogens and constitutes the major nicotine C-oxidase. A relationship between CYP2A6 genotype and smoking habits, as well as incidence of lung cancer, has been proposed. Two defective alleles have hitherto been identified, one of which is very common in Asian populations. Among Caucasians, an additional defective and frequently distributed allele (CYP2A6*3) has been suggested to play a protective role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
122
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(135 citation statements)
references
References 33 publications
11
122
1
1
Order By: Relevance
“…8 In the CYP2A6*4 (CYP2A6*4A, CYP2A6*4B, and CYP2A6*4D) alleles, the entire CYP2A6 gene is deleted and the enzymatic activity is lacking. [8][9][10][11] The CYP2A6*1X2 allele has a duplication of the CYP2A6 gene as the reciprocal product of the CYP2A6*4D allele after an unequal crossover event. 12 The CYP2A6*12 is a CYP2A7/CYP2A6 hybrid allele created by an unequal crossover in intron 2.…”
Section: Introductionmentioning
confidence: 99%
“…8 In the CYP2A6*4 (CYP2A6*4A, CYP2A6*4B, and CYP2A6*4D) alleles, the entire CYP2A6 gene is deleted and the enzymatic activity is lacking. [8][9][10][11] The CYP2A6*1X2 allele has a duplication of the CYP2A6 gene as the reciprocal product of the CYP2A6*4D allele after an unequal crossover event. 12 The CYP2A6*12 is a CYP2A7/CYP2A6 hybrid allele created by an unequal crossover in intron 2.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 A gene conversion of interest is CYP2A6*1B where the 3 0 -flanking region adjacent to exon 9 has been replaced by the corresponding CYP2A7 sequence (72 bp). 6 The subjects who possess the CYP2A6*1B allele appear to show higher capabilities of nicotine metabolism to cotinine. 7 The allele frequency of CYP2A6*1B ranges from 30% in Caucasian subjects 6 to nearly 40% in Japanese, Korean 7 and Chinese subjects 6 and up to 55% in Canadian native Indian.…”
Section: Introductionmentioning
confidence: 99%
“…6 The subjects who possess the CYP2A6*1B allele appear to show higher capabilities of nicotine metabolism to cotinine. 7 The allele frequency of CYP2A6*1B ranges from 30% in Caucasian subjects 6 to nearly 40% in Japanese, Korean 7 and Chinese subjects 6 and up to 55% in Canadian native Indian. 3 Genetic polymorphism in this gene may be of particular importance for an individual's need for nicotine.…”
Section: Introductionmentioning
confidence: 99%
“…The principal metabolic pathway of nicotine is a conversion to inactive cotinine by cytochrome P450 (CYP) 2A6.2.3 The gene encoding this enzyme, CYP2A6, has several polymorphic variants. [4][5][6][7][8] Large inter-individual differences in nicotine metabolism, including a poor metabolism phenotype with deficient cotinine formation, have been found in humans, and previous works demonstrated that the difference in nicotine metabolism is attributable to the genetic polymorphism of CYP2A6. [9][10][11][12][13] Considerable ethnic differences exist in the frequency of the inactive alleles of CYP2A6.…”
mentioning
confidence: 99%